Sustitución parcial de harina de trigo por harina de camote toquecita (Ipomoea batatas) en el perfil de calidad de galletas dulces - Muñoz Andrade, Italo Javier (2024)
The objective of this research was to obtain sweet biscuits from the partial substitution of wheat flour by sweet potato flour tocita (Ipomoea batatas L.) on bromatological, microbiological quality, quality profile and sensory. A Completely Random Design (DCA) of a single factor was applied, the treatments were composed of the percentage of sweet potato flour tocita variety (5,10, 15, 20, 25 and 30) and the percentage of wheat flour (70, 7 5, 80, 90, 95) respectively. The characterization of the sweet potato flour was carried out through physicochemical and bromatological analyzes (moisture, acidity, ashes, and control of molds and yeasts). The results obtained showed that the tocita variety sweet potato flour complies with the bromatological and microbiological parameters, complying with the maximum limits established by NTE INEN 2085. T2 (25% of tocita sweet potato flour) was the one that presented the best bromatological, microbiological and quality profile. Therefore, it is concluded that sweet potato flour is a viable and healthy alternative for the preparation of sweet cookies.